2010
DOI: 10.5194/os-6-3-2010
|View full text |Cite
|
Sign up to set email alerts
|

Density and Absolute Salinity of the Baltic Sea 2006–2009

Abstract: Abstract. The brackish water of the Baltic Sea is a mixture of ocean water from the Atlantic/North Sea with fresh water from various rivers draining a large area of lowlands and mountain ranges. The evaporation-precipitation balance results in an additional but minor excess of fresh water. The rivers carry different loads of salts washed out of the ground, in particular calcium carbonate, which cause a composition anomaly of the salt dissolved in the Baltic Sea in comparison to Standard Seawater. Directly meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 41 publications
(74 reference statements)
5
94
0
Order By: Relevance
“…(5)- (8) to enable a simple computer algorithm to deliver estimates of the Absolute Salinity S A based only on Practical Salinity S P and knowledge of location. In the Baltic Sea the approach of Feistel et al (2010) based on the Practical Salinity of the seawater sample has been used (see Eq. (12)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(5)- (8) to enable a simple computer algorithm to deliver estimates of the Absolute Salinity S A based only on Practical Salinity S P and knowledge of location. In the Baltic Sea the approach of Feistel et al (2010) based on the Practical Salinity of the seawater sample has been used (see Eq. (12)).…”
Section: Discussionmentioning
confidence: 99%
“…Millero and Kremling (1976) were the first to make density measurements using the vibrating tube densimeter technique on samples from the Baltic Sea. More recent measurements have shown that the Absolute Salinity Anomaly S A − S R = δS A in the Baltic Sea has been quite variable over the past few decades of observation (Feistel et al, 2010). The present computer algorithm uses the relationship found by Feistel et al (2010) that applies in the years 2006-2009, namely (11) where S SO = 35.16504 g kg −1 is the standard-ocean Reference Salinity that corresponds to the Practical Salinity of 35.…”
Section: Special Treatment Of Ocean Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parts of the Baltic Sea are ice covered every winter, so that the extent of the annual maximum ice cover varies between 50 × 10 3 and 340 × 10 3 km 2 (Seinä and Palosuo, 1996;Vainio, 2001) of the total area of 420 × 10 3 km 2 . The salinity varies from more than 20 ‰ in Kattegat down to less than 2 ‰ at the ends of the large bays in the northern part of the Gulf of Bothnia and Gulf of Finland (Feistel et al, 2010). In deep areas of the Baltic Proper, there is a permanent halocline somewhere between 60 and 80 m depth.…”
Section: Measurement Site and General Characteristicsmentioning
confidence: 99%
“…While the raw salinity is recorded in units according to the Practical Salinity Scale 1978, the results on salinity distribution and variability are given in the paper (Sects. 3 and 4) in g kg −1 according to Feistel et al (2010). Particular care is taken to calibrate the SCUFA fluorometer; however, since we do not use the fluorometer data in this study, the used routine is not described here.…”
Section: Quality Assurance and Pre-processing Of Datamentioning
confidence: 99%